IMPLEMENTASI SISTEM JASA PEMBANGUNAN DAN DESAIN RUMAH MENGGUNAKAN ADOBE DREAMWEAVER - Dwi Retnosari; Muhammad Haris (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
Sahmadi Design is one of the many businesses that offer services design and development of existing homes in Banjarmasin. In offering design services, Design Sahmadi still use brochures and information by word of mouth so it felt less effective in the services market. Therefore, it is necessary to have an information system in terms of promoting home design services and construction of houses through online media. Sources used to collect data in this study were interviews, observation, literature study and documentation. The tools used to analyze consists of the Data Dictionary, DFD, context diagram, and Relation Table, while the programming language used is Adobe Dreamweaver using MySQL database. The end result of this research is the creation of an information system that makes it public in knowing information about home design services and construction of houses and simplify Sahmadi Design leadership in promoting business. The output of this research is a data report design services, construction services, confirmation of payment, type of home, and quality ingredients. Keywords: Design Services , Home, Adobe Dreamweaver